REPRESENTASI KAMPUNG PRAJURIT KRATON YOGYAKARTA DALAM APLIKASI BERBASIS PERANGKAT BERGERAK - Nurnawati, Erna Kumalasari; Sutanta, Edhy; Lumaksono, Fikar Tri Putra (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2019)
Yogyakarta is a famous tourist destination city. One of the main destinations of tourists is cultural tourism, such as the palace, sites of cultural heritage, tourist villages and historic relics. One of the historical heritages that should be preserved is the Kampung Prajurit (Warrior Village). There are ten Kampung Prajurit in the Yogyakarta palace, namely Langenastran and Langenarjan, which are inside the castle of the palace, Wirobrajan, Resilience, Bugisan, Patangpuluhan, Suronggaman, Dhaengan, Jagakaryan, Mantrijeron, Prawirotaman, Jageran, Surokarsan and Nyutran who each have their own characteristics and characteristics. each other's uniqueness. Kampung Prajurit are cultural tourism assets that have not been seriously worked on, especially in terms of promotion through information technology and telecommunications. Considering the current use of mobile devices has become so widespread, the use of this media as a means of promoting the Kampung Prajurit is very urgent. Mobile-based applications can be downloaded and used easily through smartphone devices so the use of this facility to introduce Kampung Prajurit as a cultural tourism destination is very much needed. The method that will be used in this study is a qualitative method, including methods of collecting data with literature study and field observations. While the application development is done by prototyping method and application design is carried out based on the Object Oriented Analysis System with UML. While the application development uses the PHP 5.7 programming language and Android Studio 3.2.1.0 using the MySQL Admin. The result of the research is a mobile-based application prototype that will be able to display all information related to history, fashion, bregada and reality videos about activities in the warrior's village. With this application, it is expected that the Kampung Prajurit will be more widely known by the public so that tourist visits to the warrior villages will increase.